Development of Entrepreneurial University in the Conditions of Higher Education Modernization - M. K. Ibatov; Yu. N. Pak; G. S. Zhetesova; D. Yu. Pak (Высшее образование в России)
The article analyzes in the conceptual aspect the innovative activity of higher school in Kazakhstan in the context of transition to the entrepreneurial university. The necessity of implementing the concept of the entrepreneurial university in the higher education system of Kazakhstan is shown in order to develop the knowledge economy and increase the efficiency of innovative activities. The article dwells on the risks and controversial situations associated with transformation of traditional universities into new generation universities. Recommendations are given on introducing a new generation university model as a system-forming factor in the development of higher education. The need for introducing entrepreneurial culture into the educational practice of higher school has been substantiated. The authors consider the prerequisites for the formation of entrepreneurial universities in the conditions of modernization of the Kazakhstani economy.